Identifying elements of gamification for reading Music notation in music education - Jessellah Samat; Aslina Baharum; Christina Andin (IEEE Xplore, 2022)
vations related to learning music notation through audio-visual media of music notation using gamification make teaching and learning more interesting. Also, it may help improve musical notation reading. Failure to master the ability to read musical notation is the main reason most students are not interested in learning to read musical notation. Therefore, to attract the interest of notation reading in Music Education, there must be a method to overcome the problem. Improving the reading of musical notation requires various exercises by utilizing learning media. One of the exercises that can be used in learning is sight reading. Sight reading is not just conventional teaching and learning, in which the teacher explains orally, and the student memorizes the position of the musical notation on the beam. However, it utilizes the learning media that is the use of gamification because it is a method and way to increase the motivation and involvement of students in teaching and learning. This study will discuss the first phase implemented to identify gamification elements. A systematic review based on the prism model was used as the method. Results show that there are 40 gamification elements identified. Thus, using identified elements may boost students' engagement in music education.